Dr. YIN Ming＇s Experience in Treating Pediatric Diseases - 孟宪军 王文 陈炯华 肖元春 (Journal of acupuncture and tuina science, 2004)
Dr. YIN Ming is skilled at the pediatric diseases and wins the trust from her patients and their families. I learned a lot from the clinical practice with her and now the experience is as follows.